2004
DOI: 10.3748/wjg.v10.i8.1204
|View full text |Cite
|
Sign up to set email alerts
|

CT biliary cystoscopy of gallbladder polyps

Abstract: AIM:CT virtual endoscopy has been used in the study of various organs of body including the biliary tract, however, CT virtual endoseopy in diagnosis of gallbladder polyps has not yet been reported. This study was to evaluate the diagnostic value of CT virtual endoscopy in polyps of the gallbladder. METHODS:Thirty-two cases of gallbladder polyps were examined by CT virtual endoscopy, ultrasound, CT scan with oral biliary contrast separately and confirmed by operation and pathology. CT biliary cystoscopic findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…47 A single study found that CT scans with oral contrast detected only 76 of 96 (79.2%) surgically confirmed gallbladder polyps, although all missed lesions were smaller than 5 mm. 48 There are no data on the ability of MRI to identify gallbladder polyps.…”
Section: Prevalence and Risk Factors For Gallbladder Cancer In Primarmentioning
confidence: 99%
“…47 A single study found that CT scans with oral contrast detected only 76 of 96 (79.2%) surgically confirmed gallbladder polyps, although all missed lesions were smaller than 5 mm. 48 There are no data on the ability of MRI to identify gallbladder polyps.…”
Section: Prevalence and Risk Factors For Gallbladder Cancer In Primarmentioning
confidence: 99%
“…The CT diagnosis was accurate in 87% of cases however, only 5 polyps were less than 11 mm and therefore this study provides us with limited evidence regarding the role of CT in this group of patients[ 35 ]. Lou et al[ 36 ] assessed the accuracy of CT biliary cystoscopy in 32 patients and found that CUS accurately detected polyps in 96.9% of cases compared to 93.8% for CT.…”
Section: The Role Of Different Imaging Modalities In Gallbladder Polymentioning
confidence: 99%
“…Alternatively, nonenhanced and enhanced CT scan differentiate neoplastic from non-neoplastic gall bladder polyps (12). CT biliary cystoscopy has recently been suggested as a non-invasive and accurate means of assessing gall bladder polyps (13). However, in most of the units it may not be logistically practical and financially feasible to perform EUS or CT purely to differentiate gallbladder polyps.…”
Section: Discussionmentioning
confidence: 99%